MONOLIER (MONOPOLI 5R): INNOVATION OF MONOPOLY GAMES AS 5R LEARNING MEDIA FOR EARLY EDUCATION - Fardani, Fransiska Ellisa; Ramdhani, Ahmad Tajuddin; Khasanah, Amalia Nur; Ramadhani, Bayu Aji; Ananda, Meysella; Istiqomah, Nugraheni Nur; Rinawati, Seviana (Journal of Vocational Health Studies, 2018)
Background: The understanding of 5R (Ringkas, Rapi, Resik, Rawat, and Rajin) is still low among the people. This is due to the lack of early education on the 5R concept. MONOLIER (Monopoly 5R) is an inovation of learning medium that teaches students to play and learn about 5R through monopoly games. Purpose: The purpose of this researcch was to study the effect of 5R education using games "MONOLIER” to the students knowledge of 5R. Method: This was experimental study using pre-post test method. The implementation technique is the authors interact with the respondents through education material about 5R for a month in four times. Then for indicator of success of educational program using pre and post test problem which processed by wilxocon test. Population were all 4th grade students of SD N 1 Kemiri, Kebakkramat, Karanganyar as well as a sample of 37 students. This research was conducted at SDN N 1 Kemiri Kebakkramat Karanganyar Regency with the time of May 2018. The variables in this study include the level of student knowledge about 5R before and after given 5R material. Result: The result showed that there was significantly improvement of the student kowledge of 5R after education with p value 0,000 (p <0,005) . Conclusion:  The education of 5R by using MONOLIER game was effectively improve the student knowledge of 5R.